2020
DOI: 10.1007/s00421-020-04462-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased fascicle length but not patellar tendon stiffness after accentuated eccentric-load strength training in already-trained men

Abstract: Purpose This study examined whether additional external load during the eccentric phase of lower limb strength training exercises led to greater adaptations in knee extensor strength, muscle architecture, and patellar tendon properties than traditional concentric–eccentric training in already-trained men. Methods Twenty-eight men accustomed to strength training were randomized to undertake 10 weeks of supervised traditional (TRAD) or accentuated eccentric loading (AEL) or continue their habitual unsupervised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…For example, muscle damage occurred in response to experimental models that used concentric exercise (Cadore et al 2018) and isometric contractions evoked by electrical stimulation in humans (Jubeau et al 2012), as well as in response to resistance exercise consisted of maximum load climbs in animals (de Oliveira et al 2018). These findings strengthen the suggestion that the amount of muscle damage is predominantly determined by the fibre length changes instead of the muscle-tendon unit length changes (i.e., due to muscle-tendon decoupling) (Ando et al 2018;Blazevich et al 2007;Guilhem et al 2016;Hicks et al 2017;Hoffman et al 2016;Konow et al 2012;Walker et al 2020). Additionally, alterations in muscle damage indices (e.g., decrease in MVC torque) seem to be linked with the excessive muscle tension into the muscle fibre that occurs in response to negative work performed during maximal eccentric exercise (Guilhem et al 2016;Lieber et al 2002;Penailillo et al 2015).…”
Section: B3supporting
confidence: 81%
See 1 more Smart Citation
“…For example, muscle damage occurred in response to experimental models that used concentric exercise (Cadore et al 2018) and isometric contractions evoked by electrical stimulation in humans (Jubeau et al 2012), as well as in response to resistance exercise consisted of maximum load climbs in animals (de Oliveira et al 2018). These findings strengthen the suggestion that the amount of muscle damage is predominantly determined by the fibre length changes instead of the muscle-tendon unit length changes (i.e., due to muscle-tendon decoupling) (Ando et al 2018;Blazevich et al 2007;Guilhem et al 2016;Hicks et al 2017;Hoffman et al 2016;Konow et al 2012;Walker et al 2020). Additionally, alterations in muscle damage indices (e.g., decrease in MVC torque) seem to be linked with the excessive muscle tension into the muscle fibre that occurs in response to negative work performed during maximal eccentric exercise (Guilhem et al 2016;Lieber et al 2002;Penailillo et al 2015).…”
Section: B3supporting
confidence: 81%
“…However, the damaging nature of any type of exercise regularly implemented can be removed due to the repeated bout effect. Of note, the initial muscle damage and the subsequent adaptation has been suggested to be the result of changes in fascicle length and not due to changes in the muscle-tendon unit length (Ando et al 2018;Blazevich et al 2007;Guilhem et al 2016;Hicks et al 2017;Hoffman et al 2016;Konow et al 2012;Walker et al 2020). Instead, it seems that the muscle-tendon unit primarily acts as a buffer to protect muscle from the damaging nature of lengthening actions (Reeves and Narici 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that fascicle length changes could be observed already after 2 weeks including six sessions of plyometric training (+2.2%), with further increases after 4 (+4%) and 6 weeks [+4.4%; (Monti et al, 2020 )]. Our results show relatively large but nonsignificant increases in fascicle length (+13%) after 16 weeks of concurrent training with APL, similar to the changes observed with 10 weeks of accentuated eccentric loading in resistance-trained men [+14%; (Walker et al, 2020 )]. It remains to be determined whether the time course of fascicle length adaptations in elite athletes is similar to that of healthy men.…”
Section: Discussionsupporting
confidence: 83%
“…On this matter, muscles adapt their structure by adding or removing sarcomeres as a function of different training parameters, including the range at which they are stimulated 83‐85 54,64 particularly during the eccentric phase of the movement 81,86 . Consequently, the changes in fascicle length would modify the muscle function due to its influence on force‐length and force‐velocity relationships 34 …”
Section: Discussionmentioning
confidence: 99%